2016
DOI: 10.2169/internalmedicine.55.6206
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Kinetics of Th1, Th2 and Th17 Cytokines in Polymyositis Related to Chronic Graft-versus-Host Disease

Abstract: We herein describe a case of myelodysplastic syndrome with chronic graft-versus-host disease (cGVHD)-related polymyositis. On approximately day 1,570 post HLA-identical sibling bone marrow transplant, the patient presented with a fever, myalgia and liver dysfunction. A muscle biopsy revealed destruction of the muscle fibers and infiltration of CD20 + B cells and CD4 + and CD8 + T cells, and a liver biopsy confirmed the findings of cGVHD. An analysis of plasma cytokine profiles indicated elevation of not only T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Regarding CCL2, its plasma concentration seems to increase with a rise in alloreactive T cells in pulmonary and hepatic GVHD [19,20], but this effect was not observed in the intestine In silico protein-protein interaction network of up-regulated genes in patients with oGVHD and patients without GVHD. The nodes between genes represent the protein-protein interaction pairs from the STRING (Search Tool for the Retrieval of Interacting Genes/Proteins) database.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CCL2, its plasma concentration seems to increase with a rise in alloreactive T cells in pulmonary and hepatic GVHD [19,20], but this effect was not observed in the intestine In silico protein-protein interaction network of up-regulated genes in patients with oGVHD and patients without GVHD. The nodes between genes represent the protein-protein interaction pairs from the STRING (Search Tool for the Retrieval of Interacting Genes/Proteins) database.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IL-17 is the most potent inflammatory mediator in autoimmune-mediated tissue damage and in tissue injury after transplantation (Chung et al 2012; Fujino et al 2003; Gigante et al 2011). In HSCT patients, IL-17 level increases in blood and at the tissue site involved in acute or cGvHD (Chen et al 2007; Dander et al 2009; Hill et al 2010; Koh et al 2016; Liu et al 2013; Ratajczak et al 2010). Our own study on IL-17 documented that Th17 cells are rather at a low level in the blood at the onset of aGvHD likely being marginalized in the affected tissues (Dlubek et al 2010).…”
Section: Introductionmentioning
confidence: 99%